Síntese e caracterização de ZnO nanoparticulado, preparado via método sol-gel, aplicado como catalisador na degradação de cloridrato de ciprofloxacino - Bortolini, Bruna Loesch (2017)
The heterogeneous photocatalysis process is one of the treatment options for pollutants, which has presented excellent results. In this sense, the present work aims to synthesize zinc oxide (ZnO) nanoparticles and to apply it as a catalyst in the degradation of the antibiotic ciprofloxacin hydrochloride (CIP) in aqueous solution, also using UV/H2O2/ZnO. In addition, the study aims to compare the degradation action between commercial and synthesized ZnO. The experiments were followed by spectrophotometry in the UV-VIS region. In photocatalysis tests, the variables were organized in an experimental design 23 to verify the influence of each variable in the degradation process, and the experimental results were evaluated using the statistical software Statistica®. It was observed from the analysis of the results that the best conditions for the degradations process were [H2O2] = 500 mg L-1 and [ZnO] = 20 mg L-1 at pH 4, after one hour of irradiation, both for commercial ZnO and nanoparticulate.